STRATEGI PENINGKATAN RETRIBUSI PASAR YOUTEFA, SEBAGAI SALAH SATU SUMBER PENDAPATAN ASLI DAERAH - Yuli Antikasari; Westim Ratang; Agustina Sanggrangbano (Universitas Cenderawasih, 2018)
The purpose of this study is to determine changes in the organizational environment, both internal and external environments in an effort to increase the acceptance of market retribution. Descriptive research method with a qualitative approach. While the technique of collecting data with the method of documentation, in-depth interviews and direct observation. Data analysis uses interaction analysis models and SWOT analysis so that strategic issues emerge, namely: 1. Low ability and skills of employees. 2. Weak supervision and law enforcement. 3. Low level of merchant awareness of rules. 4. Practice setting targets that have not been based on existing potential. To respond to the issue, a strategy was developed as follows: Improving the quality of Human Resources through education and courses; The same understanding of organizational mission; Improvement of work procedures; socialization and counseling on rights and obligations in accordance with existing rules; cooperating with other related agencies, for example the Satong Praja Police; Persuasive and Repressive Approach; Commitments from all parties in setting targets; use actual potential data in setting targets. Keywords: Market Retribution, Acceptance, Strategy, Improvement.